2010
DOI: 10.1002/mabi.201000082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Linear Polyamines with Different Amine Spacings and their Ability to Form dsDNA/siRNA Complexes Suitable for Transfection

Abstract: In this paper we report on the synthesis of diversified linear polyamine architectures with different chain lengths and compositions and their interaction with phosphate groups of DNA/siRNA. The polyplex formation between model nucleotide (dsDNA) and these linear polyamines has been determined at different nitrogen to phosphorus (N/P) ratios using small-angle neutron scattering (SANS) and atomic force microscopy (AFM) techniques. AFM images showed that while linear poly(ethylene imine) (PEI)/DNA complex result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…From the structural point of view, polyamines used for gene transfection vary widely in their structures, which range between linear [24,[29][30][31][32][33][34][35], branched [12,30,32], hyperbranched, and perfect branched dendrimers [36]. In this chapter we present a general overview of the research reported so far using dendritic polyamines in gene delivery applications.…”
Section: Polyamines In Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…From the structural point of view, polyamines used for gene transfection vary widely in their structures, which range between linear [24,[29][30][31][32][33][34][35], branched [12,30,32], hyperbranched, and perfect branched dendrimers [36]. In this chapter we present a general overview of the research reported so far using dendritic polyamines in gene delivery applications.…”
Section: Polyamines In Gene Deliverymentioning
confidence: 99%
“…By using carbonyldiimidazole chemistry the terminal hydroxyl (-OH) groups from Boltorn were esterified with increasing equivalents (9,19,35,48, and 60) of diethylaminopropylamine (DEAPA) (Scheme 6). These polymers, which only contain ester bonds and terminal carbamate linkages, showed degradability, very low toxicity, and an ability to transfect cells.…”
Section: Hyperbranched Poly(amino Ester)smentioning
confidence: 99%
“…[26,[155][156][157][158][159][160][161][162][163] Furthermore, they can be easily modified with substitutions or additions of functional groups or by cell-or tissue-specific targeting moieties and are completely soluble in water. [164] For efficient complexation of 1 Introduction nucleic acids via electrostatic interaction, cationic polymers are used that acquire their charge from primary, secondary, tertiary, and/or quaternary amino groups.…”
Section: Cationic Polymersmentioning
confidence: 99%
“…Synthesis and structure of PEI (a) synthesis of linear PEI [161] and (b) synthesis of hyperbranched PEI [2] via acid catalyzed, ring-opening polymerization of aziridine. Each color represents a different branching unit: blue for linear units (L), black for dendritic units (D), red for terminal units (T).…”
Section: Cationic Polymersmentioning
confidence: 99%
See 1 more Smart Citation